On the formation of marxism : Karl Kautsky's Theory of Capitalism, the marxism of the Second International and Karl Marx's Critique of Political Economy - Gronow, Jukka (Helsinki : Finnish Society of Sciences and Letters, 1986)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: marxisme